(untitled) (Bangladesh Journal of Animal Science, 2014)
The PDF from another article was originally loaded for this article by mistake and on 9th February 2015 the correct PDF was loaded. A study was carried out to assess the effects of aqueousheated and dryheated Jack beans on the growth, hematology, serum metabolites and enzymes of broiler chickens. Jack beans were processed by aqueous heating into two different batches. In the first batch of aqueousheated Jack beans (AHJB1), raw seeds were soaked in distilled water for 48 hrs prior to cooking in fresh water for 1 hr The second batch (AHJB2) had raw Jack beans soaked in distilled water for 48 hrs prior to 2 hrs cooking at 1 hr interval. In preparing the dryheated Jack beans (DHJB), the raw seeds were roasted in an oven at 120°C for 30 minutes. Four hundred and twenty (420) broiler chicks of ANAK strain were randomly allotted to seven dietary groups. The aqueous heated and dryheated Jack beans were incorporated in to the diets at 15% and 30% levels respectively. Higher residual amounts of canavanine, trypsin inhibitor and haemagglutinin were retained in DHJB. The Performance characteristics showed significant (P<0.05) reductions in feed intake, body weight gain and feed conversion efficiency of birds fed 15% and 30% AHJB1 and DHJB, and 30% AHJB2, respectively. Blood studies revealed marked reductions (P<0.05) in red blood cells, packed cell volume and hemoglobin of birds fed DHJB diets. Over all, the best significant improvements in the response indices were obtained in birds fed 15% AHJB2 as the birds fed on the diet compared favorably with the control group. DOI: http://dx.doi.org/10.3329/bjas.v43i3.21650 Bang. J. Anim. Sci. 2014. 43 (3): 207-212